Strength and physical properties of sustainable concrete masonry at elevated temperature: a review - Mohd Yassin, Nurain Izzati; Adnan, Suraya Hani; Shahidan, Shahiron; Ali, Noorwirdawati; Kamarulzaman, Nurul Amirah; Abd Roni, Norwardatun (Mazedan International Research Academy, 2018)
This paper is an overview of the performance of sustainable concrete masonry containing industrial waste as cement replacement which exposed to high temperature. These industrial waste or also known as pozzolanic materials have been widely used due to their characteristic which could act as the binder in concrete. By replacing cement content in concrete this could make concrete more sustainable due to less carbon content. Based on previous researches, the performance of these sustainable concrete have been investigated in terms of its residual compressive strength and physical properties at elevated temperature. These parameters are important factor that could contribute to the structural stability and valuation of serviceability state of structure. Large numbers of research on pozzolanic concrete at elevated temperature have been conducted. Among pozzolanic materials used were fly ash, palm oil fuel ash, volcanic ash, silica fume, blast slag furnace and etc. As general according to previous research, pozzolanic concrete have better performance than OPC concrete at temperature less than 500°C. In terms of physical properties, surface cracks and discolouration of concrete has been observed. Studies show that, surface cracks on pozzolanic concrete were less than OPC concrete. Meanwhile, for discolouration impact, it was observed that, both OPC and pozzolanic concrete have similar changes in colour where the colour of concrete became lighter as the firing temperature increased. From this review it can be conclude that these industrial wastes are good in enhancing the sustainable environment as well as improving the fire resistance performance of concrete masonry.